The expansion of services in European banking: Implications for loan pricing and interest margins - Lepetit, Laetitia; Nys, Emmanuelle; Rous, Philippe; Tarazi, Amine (Journal of Banking & Finance, 2008)
Our study of 602 European banks over 1996–2002 investigates how the banks’ expansion into fee-based services has affected their interest margins and loan pricing. We find that higher income share from commissions and fees is associated with lower margins and loan spreads. The higher the commission and fee income share, moreover, the weaker the link between bank loan spreads and loan risk. The latter result is consistent with the conjecture that banks price (or misprice) loans to increase sales of other services. That loss leader (or cross selling) hypothesis has implications for bank regulation and competition with (non-bank) lenders.